Growing a Better World Together - Prowse, Victoria (2019)
Victoria Prowse SPECIAL EVENT Reducing Food Loss and Waste – Making it Personal Co-Organized by IFPRI, Stop Wasting Food / Selina Juul, World Resources Institute (WRI), Champions 12.3, and the Embassy of Denmark in Washington, DC MAR 12, 2019 - 09:30 AM TO 11:00 AM EDT